A survey of primary care resident attitudes toward continuity clinic patient handover - Victor O. Kolade; Howiada H. Salim; Mohammed Siddiqui (Greater Baltimore Medical Center, 2014)
Background: Transfer of clinic patients from graduating residents to interns or junior residents occurs every year, affecting large numbers of patients. Breaches in care continuity may occur, with potential for risk to patient safety. Several guidelines have been developed for implementing standardized inpatient sign-outs, but no specific guidelines exist for outpatient handover. Methods: Residents in primary care programs - internal medicine, family medicine, and pediatrics - at a US academic medical center were invited to participate in an online survey. The invitation was extended approximately 2 years after electronic medical record (EMR) rollout began at the institution. Results: Of 71 eligible residents, 22 (31%) responded to the survey. Of these, 18 felt that handover of ambulatory patients was at least moderately important - but only one affirmed the existence of a system for handover. IM residents perceived that they had the highest proportion of high-risk patients (p=0.042); transition-of-care letters were more important to IM residents than other respondents (p=0.041). Conclusion: There is room for improvement in resident acknowledgement of handover processes in continuity clinics. In this study, IM residents attached greater importance to a specific handover tool than other primary care residents. Thus, the different primary care specialties may need to have different handover tools available to them within a shared EMR system.